Making Hand sanitizer from Eucalyptus citriodora plants as an economic opportunity in the new normal era - Taufik, Muhammad; Syafii, M; Rahman, Arif; Hamdi; Hakim, Sukma Hayati (Talenta Publisher, 2020)
The Covid-19 pandemic that occurred in Indonesia, especially in Medan City, made people lose their jobs and had to survive to prevent the transmission of Covid-19. On average, residents who live close to infection-prone areas flock to buy masks and hand sanitizers. The supplies of hand sanitizers at various pharmacies has run out, even though the prices have gone up even ten times. This activity aims to socialize and train the making of hand sanitizers from Eucalyptus citriodora plants as an economic opportunity in the New Normal Era. The solution method is carried out by providing preparation training, extraction, and economic analysis of the availability of raw materials and the feasibility of Hand sanitizer products to the community in Tegal Sari Mandala II Village, Medan Denai District, Medan City. The results that have been achieved are hand sanitizer products made by the community and have high entrepreneurial skills in this New Normal Era. This activity is beneficial for the community, especially in terms of increasing knowledge and skills in making Hand sanitizers that can be applied to improve the economy during the Covid-19 Pandemic.